Acceleration noise due to space magnetic field for heliocentric gravitational wave detector - Jia-Hui Peng; Ji-Xiang Zhang; W. Hong; W. Su; YiWei Ni; JinHan Guo; RuiSheng Zheng (Scientific Reports)
Abstract The space-borne gravitational wave observatory is to detect low-frequency gravitational wave signals in the range of 0.1–100 mHz. The inertial sensors of space gravitational wave require very high accuracy for acceleration noise, and the interaction of the space magnetic field with the test mass can generate magnetic moment forces and Lorentz forces, which lead to acceleration noise. Here, we obtain space magnetic field data from OMNI during 25 years from 1998 to 2022. And accordingly, we calculate the acceleration noise of space magnetic field of a heliocentric gravitational wave observatory, LISA, in more than 2 solar activity cycles. Then, we obtain the amplitude spectral densities of the acceleration noise for each day of the 25 years. We find that the median of the space magnetic field acceleration noise of LISA at 1 mHz is about $$1 × \mathrm {10^{-17}~m s^{-2}~Hz^{-1/2} }$$ 1 × 10 − 17 m s − 2 H z − 1 / 2 . We compare the space magnetic field acceleration noise of LISA and a geocentric gravitational wave observatory, TianQin, and find that the acceleration noise of the space magnetic field is of comparable magnitude for TianQin and LISA, and neither of them exceeds the respective acceleration noise requirements. Based on the statistical result of space magnetic field acceleration noise in more than 2 solar cycles, we give the $$χ$$ χ – $$ξ$$ ξ parameters map of the TM for LISA and TianQin, and find that TianQin has a more stringent requirement of the parameters design than that of LISA.